Impact of preoperative stenting on the outcome of flexible ureterorenoscopy for upper urinary tract urolithiasis: a systematic review and meta-analysis - Fahmy, Omar; S. H. S. M., Hadi; Lee, C. K. S.; Khairul Asri, Mohd Ghani (S. Karger AG, 2021)
Purpose: This study aimed to investigate the effect of preoperative stenting (POS) on the perioperative outcomes of flexible ureterorenoscopy (fURS). Materials and Methods: A systematic review and meta-analysis was conducted based on the PRISMA statement. From the initially retrieved 609 reports, we excluded the ineligible studies at 2 stages. We only included studies that contained fURS patients with and without POS in the same report. Data of patients who underwent semirigid ureteroscope only were excluded from the analysis. The Newcastle-Ottawa Scale (NOS) system was applied for risk of bias assessment. Results: A total of 20 studies including 5,852 patients were involved. 48.5% of the patients had preoperative stent. Stone-free rate was significantly higher with prestenting; odds ratio (OR) was 1.98 (95% CI: 1.51–2.58) (Z = 5.02; p = 0.00001). It also displayed tendency toward lower complications; OR was 0.74 (95% CI: 0.52–1.05) (Z = 1.67; p = 0.09). POS significantly increased the use of ureteral access sheath; OR was 1.49 (95% CI: 1.05–2.13) (Z = 2.22; p = 0.03). Risk of bias assessment showed 13 and 7 studies with low and moderate risk, respectively. Conclusions: POS clearly improves the stone-free rates after fURS. It might reduce the complications, especially ureteral injury. These findings might help solve the current debate and can be useful for urologists during patient counselling for a proper decision-making.